Ogrody Dziecięce im. W.E. Raua w Warszawie w latach 1902–1906 – harmonia między sportem a zabawą - Wojewoda, Anna (Biuletyn Historii Wychowania, 2026)
Children’s Gardens W.E. Rau in Warsaw operated as a separate organization under the patronage of the Warsaw Hygienic Society. The task of this institution was to organize games and physical activities for children and teenagers. In the years 1903–1906, a total of 13 play gardens operated, of which four deserve special attention: Floriański, Agrykola, Saski and Nowogrodzki. There were separate playing fields and indoor sports halls. At that time, the Garden Committee moved away from the Prussian model when it comes to the organization and course of games. Largely thanks to Władysław Ryszard Kozłowski, inspiration was drawn from the Swedish gymnastics P.H. Ling. From that moment on, the games took place at different times with various intensities of various physical activities. In addition to team games and activities, gymnastics based on the harmonious development of the body and mind, singing and seasonal activities such as swimming lessons and bathing in the summer and sledding and playing on the ice rink in the winter were introduced. The article was devoted to the specific operation of the W. E. Rau Gardens in the years 1902–1906, i.e. in the phase of their intensive development and specialization.